The development of preterm infants from low socio-economic status families: The combined effects of melatonin, autonomic nervous system maturation and psychosocial factors (ProMote): A study protocol. - Theano Kokkinaki; Nicole Anagnostatou; Maria Markodimitraki; Theano Roumeliotaki; Manolis Tzatzarakis; Elena Vakonaki; Giorgos Giannakakis; Aristidis Tsatsakis; Eleftheria Hatzidaki (PLoS ONE)
Preterm births constitute a major public health issue and a chronic, cross-generational condition globally. Psychological and biological factors interact in a way that women from low socio-economic status (SES) are disproportionally affected by preterm delivery and at increased risk for the development of perinatal mental health problems. Low SES constitutes one of the most evident contributors to poor neurodevelopment of preterm infants. Maternal perinatal mental health disorders have persistent effects on behavioral and physiological functioning throughout the lifespan and may even be evident across generations. The overall objective of the proposed longitudinal, multi-disciplinary and multi-method study is to compare the association of psychosocial (maternal mental health, intersubjectivity, attachment, family functioning, dyadic coping and perceived social support), and biological factors (melatonin and heart rate variability) with preterm infants' development at 9 months (corrected age), between low and high SES families. We will collect data from preterm neonates (<37 weeks gestational age) hospitalized in the Department of Neonatology/Neonatal Intensive Care Unit of the University General Hospital of Heraklion, Greece, and their mothers. Data collection of psychosocial and biological factors will be carried out at birth, and at the corrected age of 6 and 9 months, while preterm infants' cognitive and social development will be assessed at 9 months corrected age. The findings of this study may highlight the need for early interventions for new mothers coming from low SES in order to promote their preterm infants' optimal early neurodevelopment and for community-evidence-based prevention efforts to restrict the cycle of health inequities and intergenerational mental disorders.